Real‐World outcomes of adalimumab in adults with non‐infectious uveitis. Issue 7 (11th March 2022) - Leal, Inês; Wong, Shiao Wei; Giuffre, Chiara; Patil, Ajay; Sousa, David Cordeiro; Barbosa‐Breda, João; Chhabra, Ramandeep; Jones, Nicholas P.; Steeples, Laura R.
ABSTRACT: Purpose: To present real‐world adalimumab (ADA) efficacy and safety outcomes in non‐infectious uveitis (NIU) from a single United Kingdom (UK) tertiary centre. Methods: Retrospective review of adult patients with NIU treated with ADA. Data were collected at baseline, 6 and 12 months. The primary goal was to evaluate the rate of treatment failure, using the VISUAL‐I/II studies criteria, during 12 months of follow‐up. Secondary aims were to quantify corticosteroid‐sparing effect; to identify safety issues; to assess change in visual acuity; to identify reasons for treatment failure and to compare treatment outcomes at 6 and 12 months for patients classified as active or inactive at baseline. Results: Fifty‐one patients (102 eyes) with mean age of 48.3 years were included. One third had a known underlying systemic disease and 47.6% had panuveitis. The most common indication for ADA was failure to respond to oral immunosuppression. Treatment failure occurred in 9/51 patients (10 eyes) after 6 months and 13/51 (20 eyes) patients after 12 months. The need for rescue treatment in the 12 months prior to ADA was significantly associated with treatment failure at 12 months. The mean prednisolone dosage was <10 mg/day at 6 and 12 months. There were no serious adverse events. Conclusion: Patients with NIU who received ADA therapy for 12 months were likely to achieve disease control, to stabilize or improve visual acuity, to experience a reduction in immunosuppression and to reduce corticosteroid dosage. No new safety events were observed.